Molecular Analysis and Chromosome Mapping of Repetitive DNAs in the Green Terror Andinoacara rivulatus (Cichlidae: Cichlasomatini) - Nirchio, Mauro; Paim, Fabilene Gomes [UNESP]; Britzke, Ricardo [UNESP]; Rossi, Anna Rita; Milana, Valentina; Oliveira, Claudio [UNESP] (Mary Ann Liebert, Inc, 2020)
Neotropical cichlids include hundreds of species whose taxonomy has benefited of molecular phylogeny and whose karyotype evolution has been related to the amount and distribution of different classes of repetitive sequences. This study provides the first integrative molecular (cytochrome c oxidase subunit 1 and 16S sequences) and cytogenetic analyses of wild samples of the green terror Andinoacara rivulatus, a cichlid naturally distributed in Ecuador and spread throughout the world as an aquarium pet. Molecular data revealed that sequences of green terror constitute a single monophyletic clade within the genus and allowed species attribution of uncertain samples previously cytogenetically analyzed. Chromosome number (2n = 48) conforms to the general trend observed within neotropical cichlids. However, mapping of different classes of repeated sequences (18S rDNA, 5S rDNA, U1 snDNA and telomeric) revealed the presence of features uncommon among representatives of these fishes, like multiple major rDNA sites, and suggested a recent occurrence of rearrangements (fusion/inversion) in two chromosome pairs.
Keywords: Cichliformes; Ecuador; heterochromatin; in situ hybridization; ITS; NORs